VEHICLE CONTROL DEVICE - YAMAGUCHI MASANOBU; MUKAI YASUHIKO; OSHIMA HIROAKI (2017)
PROBLEM TO BE SOLVED: To provide a vehicle control device which hardly imparts incongruity to a driver.SOLUTION: In a vehicle control device (1) which is used in a vehicle having steering units (35, 135) which perform steering, and a steering wheel (41) which rotates in conjunction with the steering, the vehicle control device comprises: a steering control unit (7) which performs steering by using the steering units; and a limit unit (7) which limits the rotation of the steering wheel accompanied by the steering in a first case that the steering control unit performs the steering compared with a second case that the steering control unit performs the steering resulting from a steering operation of a driver.SELECTED DRAWING: Figure 1 【課題】ドライバに不快感を与えにくい車両制御装置を提供すること。【解決手段】操舵を行う操舵ユニット（３５、１３５）、及び前記操舵と連動して回転するステアリング（４１）を備える車両に用いられる車両制御装置（１）であって、前記操舵ユニットを用いて操舵を行う操舵制御ユニット（７）と、ドライバのステアリング操舵に起因して前記操舵を行う第２の場合に比べて、前記操舵制御ユニットが前記操舵を行う第１の場合は、前記操舵に伴う前記ステアリングの回転を制限する制限ユニット（７）と、を備えることを特徴とする車両制御装置。【選択図】図１